Influence of food quality on larval growth of Atlantic bluefin tuna (Thunnus thynnus) in the Gulf of Mexico. (22nd May 2022) - Malca, Estrella; Shropshire, Taylor; Landry, Michael R; Quintanilla, Jose M; Laiz-CarriÓn, RaÚl; Shiroza, Akihiro; Stukel, Michael R; Lamkin, John; Gerard, Trika; Swalethorp, Rasmus
Abstract: Larval abundances of Atlantic bluefin tuna (ABT) in the Gulf of Mexico are currently utilized to inform future recruitment by providing a proxy for the spawning potential of western ABT stock. Inclusion of interannual variations in larval growth is a key advance needed to translate larval abundance to recruitment success. However, little is known about the drivers of growth variations during the first weeks of life. We sampled patches of western ABT larvae in 3–4 day Lagrangian experiments in May 2017 and 2018, and assessed age and growth rates from sagittal otoliths relative to size categories of zooplankton biomass and larval feeding behaviors from stomach contents. Growth rates were similar, on average, between patches (0.37 versus 0.39 mm d −1 ) but differed significantly through ontogeny and were correlated with a food limitation index, highlighting the importance of prey availability. Otolith increment widths were larger for postflexion stages in 2018, coincident with high feeding on preferred prey (mainly cladocerans) and presumably higher biomass of more favorable prey type. Faster growth reflected in the otolith microstructures may improve survival during the highly vulnerable larval stages of ABT, with direct implications for recruitment processes.